2017
DOI: 10.1039/c6ra28236a
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic adsorption of zwitterionic–xyloglucan block copolymers to CNF: towards tailored super-absorbing cellulose materials

Abstract: A biomimetic, facile approach to cellulose modification is the utilisation of self-adsorbing, naturally occurring biopolymers, such as the hemicellulose xyloglucan (XG). Herein, XG-block-poly(sulfobetaine methacrylate) (XG-b-PSBMA) zwitterionic block copolymers have been prepared and assessed for their ability to adsorb to cellulose, specifically cellulose nanofibrils (CNF). The polymers were synthesised using reversible addition-fragmentation chain-transfer ( These results highlight the advantage of using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 52 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…In our previous study, it was shown that the swelling of CNF films, only dried at room temperature, results in cavities between the layered planes. 30 Walther et al also presented a corroborating image of the layered structure from film formation and discussed the effect of the weakening of the network's internal bonding with water. 30,31 Hence, the placement of strongly adhering NPs (PDMAEMA corona) between such layered structures, with the formation of bundles of CNFs along the thickness direction, would allow for a more flexible material with prolonged plastic deformation, Fig.…”
Section: Mechanical Properties Of Cnf Nanocomposites Comparing Ex Sitmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study, it was shown that the swelling of CNF films, only dried at room temperature, results in cavities between the layered planes. 30 Walther et al also presented a corroborating image of the layered structure from film formation and discussed the effect of the weakening of the network's internal bonding with water. 30,31 Hence, the placement of strongly adhering NPs (PDMAEMA corona) between such layered structures, with the formation of bundles of CNFs along the thickness direction, would allow for a more flexible material with prolonged plastic deformation, Fig.…”
Section: Mechanical Properties Of Cnf Nanocomposites Comparing Ex Sitmentioning
confidence: 98%
“…Since it is well known that networks of CNFs are very sensitive to moisture and swell at high humidity, measurements were performed at a variety of RH-values. 3,30 The Linkam stage provided a sealed sample chamber in which the humidity could be controlled with an inlet flow of combined dry and saturated nitrogen with regulated flows. The resulting humidity control provided a tuneable test environment between 20-80% RH at room temperature.…”
Section: Mechanical Properties Of Cnf Nanocomposites Comparing Ex Sitmentioning
confidence: 99%
“…[1][2][3][4][5] Cellulosic materials often suffer from incompatibility and mixing issues with synthetic polymers, due to their inherent hydrophilic nature. Nanosized cellulose materials, nanocrystals (CNCs) and nanofibrils (CNFs), have attracted significant interest as sustainable materials for bio-nanocomposite applications, 6,7 functional materials in aero-or hydrogels, 8,9 and strong and stiff films. 5 In several strategies, CNFs or CNCs are combined with synthetic polymer matrices to increase stiffness and strength, as well as the content of renewables in the final material.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Moreover, phase transitions have been observed for cellulose derivatives mixed or grafted with other polymers. [20][21][22][23] Xanthan gums were found to be a UCST polymer as well. [24] Such materials have found increasing interest as stimuli-responsive polymers for the preparation of smart materials.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic esters like cellulose nitrate or even cellulose itself were found to exhibit UCST . Moreover, phase transitions have been observed for cellulose derivatives mixed or grafted with other polymers . Xanthan gums were found to be a UCST polymer as well .…”
Section: Introductionmentioning
confidence: 99%